Workshop : Expressive Art & Psychodrama - Fakulti Sains Kognitif dan Pembangunan Manusia, Jabatan kaunseling (2013)
Facilitator/ Trainer: En. Baharuddin Ismail Participants : 2nd year Undergraduate Counselling Students & Counselors. Objective: To expose the students with the application of Expressive Art & Psychodrama Therapy into counselling practice